Impact of Sacral Lumbal Massage on Pain and Head Decline During First Stage of Labor - Aritonang, Tetty Rina; Intarti, Wiwit Desi; Sirait, Lenny Irmawaty; Rosliana, Rosliana; Ernawati, Ernawati (Jurnal Bidan Cerdas, 2024)
Introduction: Labor pain varies in intensity, with many women experiencing high levels during delivery. This study aims to evaluate the effectiveness of sacral massage on pain intensity and fetal head descent during the first stage of labor. Method: A quantitative study was conducted with a sample of laboring mothers divided into intervention and control groups. Participants were selected using purposive sampling, with criteria including mothers aged 20-35 years, active first-stage labor, good maternal and fetal health, cephalic presentation, and uncomplicated labor. The intervention involved lumbar-sacral massage for 20 minutes, repeated once, with intervals of 5-10 minutes. The control group received relaxation through breathing exercises. The study took place from January to March 2024. Data were analyzed using the Wilcoxon and t-tests with a significance level of 0.05. Results: The intervention group significantly reduced labor pain (pre: 6.90, post: 3.70, p=0.000). There was no significant difference in fetal head descent duration between groups (p = 0.05). Conclusion: Lumbar sacral massage is an effective non-pharmacological method for reducing labor pain and is recommended for pain management in midwifery practice.